DEMOCRATIC PRINCIPLES AND THE ROLES OF TRADITIONAL POLITICAL INSTITUTIONS IN PROMOTING PEACE AND SECURITY IN NORTHERN NIGERIA: A CASE STUDY OF GOMBE STATE. - AHMED MUSA; BASHIR ABDULLAHI; MOHAMMED AUWAL; UMAR MUHAMMAD JUNGUDO (International Studies Journal)
The adoption of Western Democracy after independence has come with a lot of changes to the hitherto roles and powers of traditional political institutions of building peace and security generally inNorthern Nigeria and Gombe in particular. Until this time, the Northern Nigerian political traditional institution was no doubt the most powerful and important political institutions that were at the centre of maintaining peace and security of their people. With the advent of democratic rule in Nigeria, the powers and control of traditional political institutions began to dry up and seem to have only opportunity of stakeholders in the state with advisory position because of the systematic enforcement of political leaders who at some time lack the knowledge of their societies and are coming into power by chance which make them to represent their personal interest using democracy as a tool, rather than making their society’s interest a priority. This paper will examine the roles of traditional political institution in promoting peace and security in Northern Nigeria and look at the impact of democratic principles on traditional political institution of Northern Nigeria and Gombe State in particular. The study will use both primary and secondary sources of data. The structural functional theory will be employed to explain the topic under discussion. The findings of this study will help in shedding more light upon role of Traditional Political Institutions in Promoting Peace and Security and how the coming of Democracy undermine their power in Gombe States as well as recommend how can this institution be position for effective performance in peace building.